Development of asymmetric polysulfone and zeolitic imidazole framework 8 mixed matrix membrane for carbon dioxide and methane separation - Sapiaa Md. Nordin, Nik Abdul Hadi (2015)
Metal-Organic Framework (MOF) materials such as Zeolitic Imidazole Framework 8 (ZIF-8) have been considered among ideal filler in mixed matrix membrane (MMM) due to their good compatibility with various polymer matrices. However, limitations suffered by ZIF-8 such as commercially expensive and hardly available in small particle size and poor intrinsic separation properties have hindered its great potential. To address these issues, this study aims to synthesize and characterize ZIF-8, followed by fabricating and evaluating the performances of ZIF-8 loaded asymmetric flat sheet polysulfone (PSf) MMM for CO2/CH4 separation. ZIF- 8 was prepared via the method of aqueous room temperature media with base-type additive, triethylamine (TEA), with ratio ranging 0-0.007 to assist ZIF-8 formation. The synthesized ZIF-8s were characterized with respect to their phase crystallinity, particle size and thermal stability. The synthesis approach is considerably attractive due to relatively lower metal/ligands/solvent ratio requirement, rapid process, and high yield while retaining its intrinsic properties. The PSf/ZIF-8 MMMs incorporated with as-synthesized and heat-treated (100°C for 12 hours) ZIF-8 with different particle sizes (~100 nm, ~300 nm, and ~500 nm) were prepared via dry/wet phase inversion. The prepared membranes were evaluated with respect to their morphology, mechanical and thermal properties, and gas separation performance. Pure phase ZIF-8s were obtained with TEA/total mole ratios of 0.004-0.007 and its particle size decreased with increasing TEA ratios. The membrane characterizations as well as gas permeation test results showed that the heat-treated ZIF-8 with ~100nm particle size provided good interaction with PSf matrix. MMM loaded with 0.5wt% of heat-treated ZIF-8 produced the optimum CO2 permeance (29.22 GPU) and CO2/CH4 selectivity (23.16), while higher loading deteriorated the separation performances. Modification of ZIF-8 particle with 25mL and 50mL ammonium hydroxide solution at ice bath temperature, room temperature and 60°C was found to significantly improve its properties, i.e. phase crystallinity, pore properties and BET surface area, while preserving its overall structure. PSf/ZIF-8 MMM loaded with 0.5wt% ZIF-8 modified under 25mL ammonium hydroxide solution at 60°C increased CO2/CH4 selectivity 72% higher than neat PSf membrane, without diminishing CO2 permeance. Hence, the promising results obtained in this study demonstrates the potential of MOF, especially ZIF-8 based MMM for gas separation, specifically CO2 separation and thus warrants further investigation.